Packaging the male germline in plants - Feng, Xiaoqi; Dickinson, Hugh G. (Trends in Genetics)
The development of plant lateral organs is interesting because, although many of the same genes seem to be involved in the early growth of primordia, completely different gene combinations are required for the complete development of organs such as leaves and stamens. Thus, the genes common to the development of most organs, which generally form and polarize the primordial ‘envelope’, must at some stage interact with those that ‘install’ the functional content of the organ – in the case of the stamen, the four microsporangia. Although distinct genetic pathways of organ initiation, polarity establishment and setting up the reproductive cell line can readily be recognized, they do not occur sequentially. Rather, they are activated early and run in parallel. There is evidence for continuing crosstalk between these pathways.
Keywords: Genetics

Morphology and synaptic input of substance P receptor-immunoreactive interneurons in control and epileptic human hippocampus - Tóth, Kinga; Wittner, Lucia; Urbán, Z; Doyle, Werner K; Buzsáki, György; Ryuichi Shigemoto; Freund, Tamás F; Maglóczky, Zsófia (Neuroscience)
Substance P (SP) is known to be a peptide that facilitates epileptic activity of principal cells in the hippocampus. Paradoxically, in other models, it was found to be protective against seizures by activating substance P receptor (SPR)-expressing interneurons. Thus, these cells appear to play an important role in the generation and regulation of epileptic seizures. The number, distribution, morphological features and input characteristics of SPR-immunoreactive cells were analyzed in surgically removed hippocampi of 28 temporal lobe epileptic patients and eight control hippocampi in order to examine their changes in epileptic tissues. SPR is expressed in a subset of inhibitory cells in the control human hippocampus, they are multipolar interneurons with smooth dendrites, present in all hippocampal subfields. This cell population is considerably different from SPR-positive cells of the rat hippocampus. The CA1 (cornu Ammonis subfield 1) region was chosen for the detailed morphological analysis of the SPR-immunoreactive cells because of its extreme vulnerability in epilepsy. The presence of various neurochemical markers identifies functionally distinct interneuron types, such as those responsible for perisomatic, dendritic or interneuron-selective inhibition. We found considerable colocalization of SPR with calbindin but not with parvalbumin, calretinin, cholecystokinin and somatostatin, therefore we suppose that SPR-positive cells participate mainly in dendritic inhibition. In the non-sclerotic CA1 region they are mainly preserved, whereas their number is decreased in the sclerotic cases. In the epileptic samples their morphology is considerably altered, they possessed more dendritic branches, which often became beaded. Analyses of synaptic coverage revealed that the ratio of symmetric synaptic input of SPR-immunoreactive cells has increased in epileptic samples. Our results suggest that SPR-positive cells are preserved while principal cells are present in the CA1 region, but show reactive changes in epilepsy including intense branching and growth of their dendritic arborization.

Developing oligodendrocytes express functional GABAB receptors that stimulate cell proliferation and migration - Luyt, Karen; Slade, Timothy P; Dorward, Jienchi J; Durant, Claire F; Wu, Yue; Ryuichi Shigemoto; Mundell, Stuart J; Váradi, Anikó; Molnár, Elek (Journal of Neurochemistry)
GABAB receptors (GABABRs) are involved in early events during neuronal development. The presence of GABABRs in developing oligodendrocytes has not been established. Using immunofluorescent co-localization, we have identified GABABR proteins in O4 marker-positive oligodendrocyte precursor cells (OPCs) in 4-day-old mouse brain periventricular white matter. In culture, OPCs, differentiated oligodendrocytes (DOs) and type 2 astrocytes (ASTs) express both the GABAB1abcdf and GABAB2 subunits of the GABABR. Using semiquantitative PCR analysis with GABABR isoform-selective primers we found that the expression level of GABAB1abd was substantially higher in OPCs or ASTs than in DOs. In contrast, the GABAB2 isoform showed a similar level of expression in OPCs and DOs, and a significantly higher level in ASTs. This indicates that the expression of GABAB1 and GABAB2 subunits are under independent control during oligodendroglial development. Activation of GABABRs using the selective agonist baclofen demonstrated that these receptors are functionally active and negatively coupled to adenylyl cyclase. Manipulation of GABABR activity had no effect on OPC migration in a conventional agarose drop assay, whereas baclofen significantly increased OPC migration in a more sensitive transwell microchamber-based assay. Exposure of cultured OPCs to baclofen increased their proliferation, providing evidence for a functional role of GABABRs in oligodendrocyte development. The presence of GABABRs in developing oligodendrocytes provides a new mechanism for neuronal-glial interactions during development and may offer a novel target for promoting remyelination following white matter injury.

Number and density of AMPA receptors in individual synapses in the rat cerebellum as revealed by SDS-digested freeze-fracture replica labeling - Masugi-Tokita, Miwako; Tarusawa, Etsuko; Watanabe, Masahiko; Molnár, Elek; Fujimoto, Kazushi; Ryuichi Shigemoto (Journal of Neuroscience)
The number of AMPA receptor (AMPAR) is the major determinant of synaptic strength at glutamatergic synapses, but little is known about the absolute number and density of AMPARs in individual synapses. Using SDS-digested freeze-fracture replica labeling, which has high detection efficiency comparable with electrophysiological noise analysis for functional AMPAR, we analyzed three kinds of excitatory synapses in the molecular layer of the adult rat cerebellum. In parallel fiber (PF)-Purkinje cell (PC) synapses, we found large variability in the number (38.1 ± 34.4 particles per synapse, mean ± SD; range, 2-178 particles per synapse) and density (437 ± 277 particles/μm2; range, 48-1210 particles/μm2) of immunogold-labeled AMPARs. Two-dimensional view and high sensitivity of this method revealed irregular-shaped small AMPAR clusters within synapses. Climbing fiber (CF)-PC synapses had higher number of AMPAR labeling (68.6 ± 34.5 particles per synapse) than PF-PC and PF-interneuron synapses (36.8 ± 14.4 particles per synapse). Furthermore, AMPAR density at CF-PC and PF-interneuron synapses was approximately five times higher and more uniform than that at PF-PC synapses. These results suggest input- and target-dependent regulation of AMPAR-mediated synaptic strength.

Functional presynaptic HCN channels in the rat globus pallidus - Boyes, Justin; Bolam, John P; Ryuichi Shigemoto; Stanford, Ian M (European Journal of Neuroscience)
Hyperpolarization-activated, cyclic nucleotide-gated cation (HCN) channels are expressed postsynaptically in the rodent globus pallidus (GP), where they play several important roles in controlling GP neuronal activity. To further elucidate the role of HCN channels in the GP, immunocytochemical and electrophysiological approaches were used to test the hypothesis that HCN channels are also expressed presynaptically on the local axon collaterals of GP neurons. At the electron microscopic level, immunoperoxidase labelling for HCN1 and HCN2 was localized in GP somata and dendritic processes, myelinated and unmyelinated axons, and axon terminals. One population of labelled terminals formed symmetric synapses with somata and proximal dendrites and were immunoreactive for parvalbumin, consistent with the axon collaterals of GABAergic GP projection neurons. In addition, labelling for HCN2 and, to a lesser degree, HCN1 was observed in axon terminals that formed asymmetric synapses and were immunoreactive for the vesicular glutamate transporter 2. Immunogold labelling demonstrated that HCN1 and HCN2 were located predominantly at extrasynaptic sites along the plasma membrane of both types of terminal. To determine the function of presynaptic HCN channels in the GP, we performed whole-cell recordings from GP neurons in vitro. Bath application of the HCN channel blocker ZD7288 resulted in an increase in the frequency of mIPSCs but had no effect on their amplitude, implying that HCN channels tonically regulate the release of GABA. Their presence, and predicted role in modulating transmitter release, represents a hitherto unidentified mechanism whereby HCN channels influence the activity of GP neurons.

Quantitative analysis and subcellular distribution of mRNA and protein expression of the hyperpolarization-activated cyclic nucleotide-gated channels throughout development in rat hippocampus - Brewster, Amy L; Chen, Yuncai; Bender, Roland A; Yeh, Amy; Ryuichi Shigemoto; Baram, Tallie Z (Cerebral Cortex)
The properties of the hyperpolarization-activated current (Ih) and its roles in hippocampal network function evolve radically during development. Because Ih is conducted by the hyperpolarization- activated cyclic nucleotide-gated (HCN) cation channels, we tested the hypothesis that understanding the quantitative developmental profiles of HCN1, HCN2, and HCN4 expression, and the isoform- and age-specific progression of their subcellular distribution, should shed light on the established modifications of the properties of Ih throughout development. Combined quantitative in situ hybridization, regional western blots, and high-resolution, dual-label immunocytochemistry revealed striking and novel information about the expression and distribution of the HCN channel isoforms in the developing hippocampal formation. In cornus ammon 1 (CA) pyramidal cell layer, a robust increase of HCN1 mRNA and protein expression occurred with age, with reciprocal reduction of HCN4 and relatively stable HCN2 levels. These distinct expression patterns raised the contribution of HCN1 to the total HCN channel pool from 33% to 65% consonant with acceleration and reduced cyclic adenosine mono phosphate (cAMP) sensitivity of Ih in this region with age. In CA3, strong expression of HCN1 already neonatally supports the recently established role of this conductance in neonatal, age-specific, hippocampal oscillations (giant depolarizing potentials). Notably, HCN1 channels were present and probably transported to dendritic compartments already on postnatal day (P) 2, whereas HCN2 channel protein was not evident in dendrites for the first 2 weeks of life. HCN2 mRNA and protein expression remained fairly constant subsequent to the first week of life in all hippocampal subfields examined, whereas HCN4 mRNA and protein expression declined after maximal neonatal expression, so that the contribution of this isoform to the total HCN channel pool dropped from 43% (CA1) and 34% (CA3) on P11 to 8% (CA1) and 19% (CA3) on P90. Interneuronal expression of all HCN channel isoforms in stratum pyramidale was robust in parvalbumin-but not in cholecystokinin-expressing populations and with a subunit-specific subcellular distribution. Taken together, these data suggest that early in life, HCN4 may contribute significantly to the functions of Ih in specific hippocampal regions. In addition, these evolving, differential quantitative, and subcellular expression patterns of the HCN channel isoforms support age-specific properties and functions of Ih within the developing hippocampal formation.

High-resolution quantitative visualization of glutamate and GABA receptors at central synapses - Masugi-Tokita, Miwako; Ryuichi Shigemoto (Current Opinion in Neurobiology)
Glutamate and GABA are the main transmitters in the central nervous system and their effects are mediated by ionotropic and metabotropic receptors. Immunogold electron microscopy has revealed the quantitative localization of these receptors at 20-30 nm resolution. SDS-digested freeze-fracture replica labeling (SDS-FRL), a newly developed immunogold method, provides an accurate estimate of molecule numbers. Here, we summarize the recent advances in quantitative receptor localization, including use of SDS-FRL analyses to determine numbers of AMPA-type glutamate receptors in the cerebellum. The two-dimensional view and high sensitivity of SDS-FRL have revealed small, irregularly shaped AMPA receptor clusters within cerebellar synapses.

Localization of HCN1 channels to presynaptic compartments: Novel plasticity that may contribute to hippocampal maturation - Bender, Roland A; Kirschstein, Timo; Kretz, Oliver; Brewster, Amy L; Richichi, Cristina; Rüschenschmidt, Christiane; Ryuichi Shigemoto; Beck,Heinz; Frotscher, Michael; Baram, Tallie Z (Journal of Neuroscience)
Increasing evidence supports roles for the current mediated by hyperpolarization-activated cyclic nucleotide-gated (HCN) channels, I h, in hippocampal maturation and specifically in the evolving changes of intrinsic properties as well as network responses of hippocampal neurons. Here, we describe a novel developmental plasticity of HCN channel expression in axonal and presynaptic compartments: HCN1 channels were localized to axon terminals of the perforant path (the major hippocampal afferent pathway) of immature rats, where they modulated synaptic efficacy. However, presynaptic expression and functions of the channels disappeared with maturation. This was a result of altered channel transport to the axons, because HCN1 mRNA and protein levels in entorhinal cortex neurons, where the perforant path axons originate, were stable through adulthood. Blocking action potential firing in vitro increased presynaptic expression of HCN1 channels in the perforant path, suggesting that network activity contributed to regulating this expression. These findings support a novel developmentally regulated axonal transport of functional ion channels and suggest a role for HCN1 channel-mediated presynaptic I h in hippocampal maturation.

HCN2 and HCN4 isoforms self-assemble and co-assemble with equal preference to form functional pacemaker channels - Whitaker, Gina M; Angoli, Damiano; Nazzari, Hamed; Ryuichi Shigemoto; Accili, Eric A (Journal of Biological Chemistry)
Hyperpolarization-activated cyclic nucleotide-modulated (HCN) "pacemaker" channel subunits are integral membrane proteins that assemble as tetramers to form channels in cardiac conduction tissue and nerve cells. Previous studies have suggested that the HCN2 and HCN4 channel isoforms physically interact when overexpressed in mammalian cells, but whether they are able to co-assemble and form functional channels remains unclear. The extent to which co-assembly occurs over self-assembly and whether HCN2-HCN4 heteromeric channels are formed in native tissue are not known. In this study, we show co-assembly of HCN2 and HCN4 in live Chinese hamster ovary cells using bioluminescence resonance energy transfer (BRET2), a novel approach for studying tetramerization of ion channel subunits. Together with results from electrophysiological and imaging approaches, the BRET2 data show that HCN2 and HCN4 subunits self-assemble and co-assemble with equal preference. We also demonstrate colocalization of HCN2 and HCN4 and a positive correlation of their intensities in the embryonic mouse heart using immunohistochemistry, as well as physical interactions between these isoforms in the rat thalamus by coimmunoprecipitation. Together, these data support the formation of HCN2-HCN4 heteromeric channels in native tissue.

The coexistence of multiple receptors in a single nerve terminal provides evidence for pre-synaptic integration - Ladera, Carolina; Godino, María D; Martín, Ricardo J; Luján, Rafael; Ryuichi Shigemoto; Ciruela, Francisco; Torres, Magdalena; Sánchez-Prieto, José (Journal of Neurochemistry)
Excitatory synaptic transmission is inhibited by G protein coupled receptors, including the adenosine A1, GABAB, and metabotropic glutamate receptor 7. These receptors are present in nerve terminals where they reduce the release of glutamate through activating signaling pathways negatively coupled to Ca2+ channels and adenylyl cyclase. However, it is not clear whether these receptors operate in distinct subpopulations of nerve terminals or if they are co-expressed in the same nerve terminals, despite the functional consequences that such distributions may have on synaptic transmission. Applying Ca2+ imaging and immunocytochemistry, we show that these three G protein coupled receptors coexist in a subpopulation of cerebrocortical nerve terminals. The three receptors share an intracellular signaling pathway through which their inhibitory responses are integrated and coactivation of these receptors produced an integrated response. Indeed, this response was highly variable, from a synergistic response at subthreshold agonist concentrations to an occluded response at high agonist concentrations. The presence of multiple receptors in a nerve terminal could be responsible for the physiological effects of neurotransmitter spillover from neighboring synapses or alternatively, the co-release of transmitters by the same nerve terminal.

Recent developments in quantum mechanics with magnetic fields - László Erdös (Spectral Theory and Mathematical Physics: a Festschrift in Honor of Barry Simon's 60th Birthday)

Rigorous derivation of the Gross-Pitaevskii equation - László Erdös; Schlein, Benjamin; Yau, Horng-Tzer (Physical Review Letters)
The time-dependent Gross-Pitaevskii equation describes the dynamics of initially trapped Bose-Einstein condensates. We present a rigorous proof of this fact starting from a many-body bosonic Schrödinger equation with a short-scale repulsive interaction in the dilute limit. Our proof shows the persistence of an explicit short-scale correlation structure in the condensate.

Derivation of the cubic non linear Schrödinger equation from quantum dynamics of many body systems - László Erdös; Schlein, Benjamin; Yau, Horng-Tzer (Inventiones Mathematicae)
We prove rigorously that the one-particle density matrix of three dimensional interacting Bose systems with a short-scale repulsive pair interaction converges to the solution of the cubic non-linear Schrödinger equation in a suitable scaling limit. The result is extended to k-particle density matrices for all positive integer k.

Quantum diffusion of the random Schrödinger evolution in the scaling limit II. The recollision diagrams - László Erdös; Salmhofer, Manfred; Yau, Horng-Tzer (Communications in Mathematical Physics)
We consider random Schrödinger equations on ℝd for d ≥ 3 with a homogeneous Anderson-Poisson type random potential. Denote by λ the coupling constant and ψt the solution with initial data ψ0. The space and time variables scale as χ ≃λ-2-κ/2, t ≃λ-2-κ with 0 < kappa; < kappa;0(d). We prove that, in the limit λ → 0, the expectation of the Wigner distribution of ψt converges weakly to the solution of a heat equation in the space variable x for arbitrary L2 initial data. The proof is based on a rigorous analysis of Feynman diagrams. In the companion paper [10] the analysis of the non-repetition diagrams was presented. In this paper we complete the proof by estimating the recollision diagrams and showing that the main terms, i.e. the ladder diagrams with renormalized propagator, converge to the heat equation.

Quantum diffusion for the Anderson model in the scaling limit - László Erdös; Salmhofer, Manfred; Yau, Horng-Tzer (Annales Henri Poincare)
We consider random Schrödinger equations on ℤd for d ≥ 3 with identically distributed random potential. Denote by λ the coupling constant and ψ t the solution with initial data ψ 0. The space and time variables scale as x ∼ λ -2-κ/2,t ∼ λ-2-κ with 0 < κ < κ0(d). We prove that, in the limit λ → 0, the expectation of the Wigner distribution of ψ t converges weakly to a solution of a heat equation in the space variable x for arbitrary L 2 initial data. The diffusion coefficient is uniquely determined by the kinetic energy associated to the momentum υ. This work is an extension to the lattice case of our previous result in the continuum [8,9]. Due to the non-convexity of the level surfaces of the dispersion relation, the estimates of several Feynman graphs are more involved.

Decay of the Fourier transform of surfaces with vanishing curvature - László Erdös; Salmhofer, Manfred (Mathematische Zeitschrift)
We prove L p -bounds on the Fourier transform of measures μ supported on two dimensional surfaces. Our method allows to consider surfaces whose Gauss curvature vanishes on a one-dimensional submanifold. Under a certain non-degeneracy condition, we prove that μ ∧ ε L 4+β, β > 0, and we give a logarithmically divergent bound on the L 4-norm. We use this latter bound to estimate almost singular integrals involving the dispersion relation, e(p)= ∑13 [1-\cos p_j]} , of the discrete Laplace operator on the cubic lattice. We briefly explain our motivation for this bound originating in the theory of random Schrödinger operators.

Turbulence transition in pipe flow - Eckhardt, Bruno; Schneider, Tobias M; Björn Hof; Westerweel, Jerry (Annual Review of Fluid Mechanics)
Pipe flow is a prominent example among the shear flows that undergo transition to turbulence without mediation by a linear instability of the laminar profile. Experiments on pipe flow, as well as plane Couette and plane Poiseuille flow, show that triggering turbulence depends sensitively on initial conditions, that between the laminar and the turbulent states there exists no intermediate state with simple spatial or temporal characteristics, and that turbulence is not persistent, i.e., it can decay again, if the observation time is long enough. All these features can consistently be explained on the assumption that the turbulent state corresponds to a chaotic saddle in state space. The goal of this review is to explain this concept, summarize the numerical and experimental evidence for pipe flow, and outline the consequences for related flows.

Lifetime of turbulence in pipe flow - Björn Hof; Tax, Wilco; Westerweel, Jerry

When three is not a crowd a Crossregulation Model of the dynamics and repertoire selection of regulatory CD4 T cells - Carneiro, Jorge; Leon, Kalet; Caramalho, Íris; Van Den Dool, Carline; Gardner, Rui; Oliveira, Vanessa; Bergman, Marie L; Sepúlveda, Nuno; Tiago Paixao; Faro, Jose; Demengeot, Jocelyne (Immunological Reviews)
Summary: Regulatory CD4+ T cells, enriched in the CD25 pool of healthy individuals, mediate natural tolerance and prevent autoimmune diseases. Despite their fundamental and potential clinical significance, regulatory T (TR) cells have not yet been incorporated in a coherent theory of the immune system. This article reviews experimental evidence and theoretical arguments supporting a model of TR cell dynamics, uncovering some of its most relevant biological implications. According to this model, the persistence and expansion of TR cell populations depend strictly on specific interactions they make with antigen-presenting cells (APCs) and conventional effector T (TE) cells. This three-partner crossregulation imposes that TR cells feed on the specific autoimmune activities they suppress, with implications ranging from their interactions with other cells to their repertoire selection in the periphery and in the thymus, and to the relationship between these cells and the innate immune system. These implications stem from the basic prediction that the peripheral dynamics sort the CD4+ T-cell repertoire into two subsets: a less diverse set of small clones of autoreactive effector and regulatory cells that regulate each other’s growth, and a more diverse set of barely autoreactive TE cell clones, whose expansion is limited only by APC availability. It is argued that such partitioning of the repertoire sets the ground for self–non-self discrimination.

Quantitative insights into stochastic monoallelic expression of cytokine genes - Tiago Paixao; Carvalho, Tiago P; Calado, Dinis P; Carneiro, Jorge (Immunology and Cell Biology)
Gene expression from both parental alleles is beneficial by masking the effects of deleterious recessive mutations and by reducing the noise in gene expression in diploid organisms. However, a class of genes are expressed preferentially or strictly from a single allele. The selective advantage of avoiding biallelic expression is clear for allelic-excluded antigen receptor and odorant receptor genes, genes undergoing X-chromosome inactivation in females and parental genomic imprinted genes. In contrast, there is no clear biological rationale for the predominant and stochastic monoallelic expression of cytokine genes in the immune system, and the underlying mechanism is elusive and controversial. A clarification of the mechanism of predominant monoallelic expression would be instrumental in better understanding its eventual biological functional. This prompted the development of a quantitative framework that could describe the dynamics of the pattern of allele expression of the IL-10 gene, from which general quantitative insights could be gained. We report that the experimental observations on these patterns of allelic expression cannot be easily reconciled with a simple model of stochastic transcriptional activation, in which the two alleles are, at any time, equally competent for transcription. Instead, these observations call into action a general model of eukaryotic transcriptional regulation according to which the locus competence for transcription is dynamic, involving multiple, cooperative and stochastic modification steps. In this model, the probability that an allele becomes transcriptionally active is a function of the number of chromatin modifications that it accumulated. On the basis of the properties of this model, we argue that predominant monoallelic expression might have had no adaptive role, and may have evolved under indirect selection for low frequency of expressing cells.